2017
DOI: 10.1039/c6cp07308e
|View full text |Cite
|
Sign up to set email alerts
|

Exciton-vibrational resonance and dynamics of charge separation in the photosystem II reaction center

Abstract: The dynamics of charge separation in the photosystem II reaction center (PSII-RC) in the presence of intramolecular vibrations with their frequency matching the energy gap between the exciton state acting as the primary electron donor and the first charge-transfer (CT) state are investigated. A reduced PSII-RC 4-state model explicitly including a CT state is analyzed within Redfield relaxation theory in the multidimensional exciton-vibrational (vibronic) basis. This model is used to study coherent energy/elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 48 publications
3
84
0
Order By: Relevance
“…1). This vibronic mechanism has been proposed and described by theoretical methods [14][15][16][17][18][19][20][21] and later demonstrated by combined experimental-theoretical approaches [11][12][13][22][23][24] . In our previous work 12 , two-dimensional electronic spectroscopy (2DES) [25][26] and Fourier transform (FT) analysis allowed to visualize the coherence between electronic states in 2D frequency maps [obtained by Fourier transformation of the real rephasing 2D spectra along the population time (T)].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…1). This vibronic mechanism has been proposed and described by theoretical methods [14][15][16][17][18][19][20][21] and later demonstrated by combined experimental-theoretical approaches [11][12][13][22][23][24] . In our previous work 12 , two-dimensional electronic spectroscopy (2DES) [25][26] and Fourier transform (FT) analysis allowed to visualize the coherence between electronic states in 2D frequency maps [obtained by Fourier transformation of the real rephasing 2D spectra along the population time (T)].…”
Section: Introductionmentioning
confidence: 97%
“…These maps display features corresponding only to the states oscillating at a certain frequency and, therefore, are more selective than the 2D spectra. Moreover, two main 2D frequency maps characteristics: i) the oscillation frequency (in or out of resonance with the electronic states energy gaps), and ii) the position of the most intense bands (corresponding or not to the states in resonance with the oscillation frequency); provide an invaluable tool to classify the observed coherences as mainly electronic, mixed electronic-vibrational (vibronic) or mainly vibrational 11,13,[27][28] . We found that three main frequency modes, 120, 340 and 730 cm -1 , representative of mainly electronic, mixed electronic-vibrational (vibronic) and mainly vibrational coherence, respectively, dominate the oscillatory dynamics 11,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we focused only on the charge separation starting from the accessory Chl * D1 . As was discussed by Romero et al 15,52 and Fuller et al, 16 however, the charge separation from the special pair (P D1 P D2 ) * cannot be easily discounted. Detailed analyses on the special pair are left for future studies.…”
mentioning
confidence: 95%
“…(a particular case of Eq. (20)). The results of the calculations of the electronic coherence σ 21 (t) within Förster theory according to the derived formula (45) with and without the non-equilibrium correction (54) in comparison with HEOM is presented on Fig.…”
Section: A Förster Theorymentioning
confidence: 99%